Assessment of spinal cord relative vulnerability in C4–C5 compressive cervical myelopathy using multi-modal spinal cord evoked potentials and neurological findings. (4th July 2021) - Imajo, Yasuaki; Kanchiku, Tsukasa; Suzuki, Hidenori; Nishida, Norihiro; Funaba, Masahiro; Taguchi, Toshihiko; Sakai, Takashi
Abstract : Objective: The correlation between the progression of spinal cord lesions using spinal cord evoked potentials (SCEPs) and neurological findings are unclear. The purpose is to electrophysiologically evaluate relative vulnerability of spinal cord in patients with compressive cervical myelopathy (CCM) at C4–C5 intervertebral level using SCEPs and correlate the progression of spinal cord lesions with neurological findings. Design: Retrospective study. Setting: Yamaguchi University Hospital. Participants: 36 patients. Methods: SCEPs following median nerve stimulation (MN-SCEPs), ulnar nerve stimulation (UN-SCEPs), transcranial electric stimulation (TCE-SCEPs), and spinal cord stimulation (SC-SCEPs) were intraoperatively recorded. MN-SCEPs are mediated by posterior horns (4, 5 layers), UN-SCEPs by the Burdach tract, TCE-SCEPs by the lateral corticospinal tract, and SC-SCEPs by the Goll tract. We evaluated the neurological findings (numbness, tactile sense and pain sense in the C6 area, tactile sense in the lower extremities, and triceps tendon reflex [TTR]). Results: The incidence of electrophysiological and clinical abnormalities decreased in the order of UN-SCEPs (100%), TCE-SCEPs (94.4%), MN-SCEPs (77.8%), and SC-SCEPs (69.4%), and in the order of numbness (100%), pain sense (97.2%), TTR (91.7%), tactile sense in the C6 area (83.3%), and tactile sense in the lower extremities (70.0%), respectively. Conclusions: The relative vulnerability of spinal cord occurred in the order of the Burdach tract, the lateral corticospinal tract, posterior horns (4, 5 layers), and the Goll tract in most patients with CCM at the C4–C5 intervertebral level.